VISUALISASI MOTIF TENUN HASIL ANAK USIA DINI DI SUKU BADUY LUAR - Nina Maftukha (Universitas Mercu Buana, 2019)
Visualization is the expression of an idea or feeling by using pictures, writing (words and numbers), maps, graphics, and so on. Visualization of weaving motifs of early childhood results in the Baduy Tribe has varied patterns as a representation of the development of local children's creativity.The objective to be achieved in this study is to examine the visualization of weaving results of early childhood in the Baduy Tribe with qualitative methods with visual anthropology and semiotics approaches. This is very important to be studied to formulate the process of creativity of young children in learning to weave.The results of the study concluded that the development of children in terms of making motifs can be classified in stages, namely, children aged 2 years, 3 years, 3.5 years, 4 years, 5 years and 6 years. The difference is in terms of structure, weft and weaving technique, and the choice of thread color for a motif.These creative methods and processes in the future will be applied to early childhood learning systems, then the final results can be formulated and this research can be developed more broadly so that they can be used as a reference in other linear studies. The specific target to be achieved in this research is the publication of journals, as well as book chapters that can be used as scientific support books.